Ramadan al-Mubarak: towards a better ummah / Muhammad Yusuf Abdul Zaid, Muhammad ‘Izzuddin Zamery and Zakiah Mohd Noordin - Abdul Zaid, Muhammad Yusuf; Zamery, Muhammad ‘Izzuddin; Mohd Noordin, Zakiah (Faculty of Pharmacy, 2023)
The month of Ramadan is a special month for the Muslim community, where they fast throughout the month, perform additional night prayers and recite the Quran more frequently to strengthen their relationship with Allah S.W.T. The Faculty of Pharmacy Student Secretariat (SMF) 2022/2023 and Society of Pharmacy Students (SOPHYS) 2022/2023 organised various activities to assist students preparing mentally, spiritually, and practically for the blessed month.